Estudio de viabilidad tecnico-economica para la conversion de hornos electricos en hornos a gas natural - Sobrinho, P. M.; Silveira, J. L.; Carvalho, J. A. (My University, 2000)
Technical and economic feasibility of using natural gas as a non-polluting energy source was studied. Conversion of electric ovens to gas-fired ovens for the preparation of aluminum plates for laminations was used as an example of this application. Four cases were evaluated for the use of heat derived from residual gases following combustion of the natural gas. Additionally, two possibilities are included for the use of systems of co-generation; one using an internal combustion engine, and second using a gas turbine. Results suggested that it was technically and economically feasible to convert the electric ovens considered to natural gas-operated ovens.
Study of the technical and economic feasibility for the conversion of electric furnaces to operation with natural gas
Keywords: Cogeneration plants; Cost effectiveness; Electric power generation; Natural gas; Natural gas-operated ovens; Electric furnaces